2014
DOI: 10.1001/jamapediatrics.2014.900
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Cardiovascular Risk in Overweight Preschool Children

Abstract: IMPORTANCETo date, the relationship among adiposity, insulin resistance, and cardiovascular risk factors at the onset of overweight or obesity has been unexplored.OBJECTIVES To assess whether insulin resistance and metabolic abnormalities are detectable at the onset of obesity and to unravel the interplay among adiposity, insulin resistance, and other such abnormalities. DESIGN, SETTING, AND PARTICIPANTSThe Origin of Cardiovascular Risk in Overweight Preschool Children cohort study aimed to evaluate at the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 41 publications
3
31
1
1
Order By: Relevance
“…We demonstrate therewith and in keeping with a previous observation of us [6] that obesity starts affecting HOMA-IR very early in childhood. In the present series, we saw a progressively increase in HOMA-IR values in both sexes from 5 to 7 years of age even in normal-weight children.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We demonstrate therewith and in keeping with a previous observation of us [6] that obesity starts affecting HOMA-IR very early in childhood. In the present series, we saw a progressively increase in HOMA-IR values in both sexes from 5 to 7 years of age even in normal-weight children.…”
Section: Discussionsupporting
confidence: 93%
“…The EarlyBird study 26, a prospective cohort study of 235 healthy children aged 5-14 years, reported a progressive increase in HOMA-IR by 7 years of age onward in normal-weight children [2]. Importantly, both studies [2,6] suggest that IR starts to increase years before the beginning of the pubertal development and findings from the present series confirm this observation. On the contrary, D'Annunzio et al [27] did not observe any agerelated difference of HOMA-IR values in 142 prepubertal normal-weight Italian children who were cross-sectionally evaluated.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3 In the Bogalusa Heart Study, in all children with a body mass index (BMI) ≥99th percentile, obesity persisted into adulthood. 4 Furthermore, obesity can lead to metabolic abnormalities before age 5 years, 5 and severe obesity in childhood carries short-, medium-, and longer-term cardiovascular risks that exceed those of their less-obese peers. 6 All of these factors suggest an elevated lifetime risk of cardiometabolic disease in children with severe obesity, with a proportion of these children at risk for requiring bariatric surgery as early as adolescence.…”
mentioning
confidence: 99%
“…Increases in adiposity associated with childhood obesity is a risk factor for glucose intolerance, insulin resistance, dyslipidemia, non-alcoholic fatty liver disease, hypertension, heart attack, stroke and premature death (2)(3)(4)(5)(6). Although body mass index (BMI) is widely used as an index of body fat (BF), it is not a direct measurement of adiposity.…”
Section: Introductionmentioning
confidence: 99%